P32 Using simulation to prepare medical students to assess and manage an acutely unwell and suicidal patient. (3rd November 2019) - Mcgowan, Ella; Leach, Helen
Abstract : Background: Simulation in undergraduate medical education often focuses on the assessment and management of an acutely unwell patient 1, whilst communication skills needed to assess a mentally unwell patient tends to be taught through role player 2 . We wanted to combine the two presentations to reflect on real life practice and to help prepare the students for assessment of an acutely medically ill patient who also is also suicidal. Summary of work: This simulation session was implemented for 67 final year medical students on the Acutely Ill Patient (AIP) module. The scenario involved a faculty member acting as a patient who had taken a large overdose of paracetamol and alcohol with the intention of ending their life, who was initially compliant with the clinical assessment but then decides they want to go home. The patient had pictures of cuts attached to her forearms and appeared disheveled. The scenario was developed for the students to practice assessing capacity and risk whilst continuing with medical management in a safe space where the situation would be debriefed with trained faculty and a toxicology consultant. Summary of results: The students' opinions were collected using SurveyMonkey via QR codes and we received a total of 48 responses. We found that 56% of the students strongly agreed with the statement 'I feel more confident managing acutely ill patients with this presentation' and 60% strongly agreed with the statement 'I am more aware of the non-technical skills required in clinical practice'. One student felt 'the simulation was very useful and a different style to most enabling communication to be explored more fully'. Discussion and conclusions: Our students were able to practice assessing a patient who was refusing medical treatment whilst lacking mental capacity and they appreciated the need for sensitive communication and the importance of utilising the other members of the team including security services. Our faculty member, who was a Clinical Teaching Fellow, was able to act as a tearful then angry patient and we recognise that not all departments would have faculty with these skills. For this scenario to be successful the students should have prior experience in simulation. Recommendations: Simulation can be used to aid in the teaching of risk assessment for a suicidal patient in addition to the medical management. When communication is a vital part of assessment a real person playing the patient can improve the fidelity. References: Issenberg S.B., McGaghie W.C., Petrusa E.R., Gordon L. D., Scalese R.J. (2005) 'Features and uses of high- fi delity medical simulations that lead to effective learning: a BEME systematic review', Medical Teacher 27 : 10 – 28 McNaughton, N., Ravitz, P., Wadell, A., Hodges, B. (2008). 'Psychiatric Education and Simulation: A Review of the Literature.' The Canadian Journal of Psychiatry, 53(2), pp.85–93.